2019
DOI: 10.29252/mlj.13.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antibiotic Resistance Pattern and frequency of CTX-M, TEM, and SHV Β-Lactamase Encoding Genes among Shigella Isolates from Inpatients in Tehran, Iran

Abstract: Background and Objectives: The emergence of extended-spectrum β-lactamase (ESBL)-producing Shigella spp. is becoming a health concern worldwide. This study aimed to investigate antibiotic resistance pattern and frequency of blaCTX-M, blaSHV, and blaTEM genes among Shigella isolates from patients in hospitals of Tehran, Iran. Methods: In this cross-sectional study, 52 non-repeated Shigella strains were isolated from hospitalized patients in Milad, Emam Khomeini and Shariati hospitals in Tehran (Iran) from Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In our study, we found a high rate of resistance to trimethoprim-sulfamethoxazole, cefazolin, and ampicillin in Shigella isolates. Theas resistance rates were in agreement with the reports published by Zamanlou et al [18], Nodeh Farahani et al [31], and Wang et al [32] in Iran and China, but higher than the results obtained by other researchers from China [33] to cefazolin, and Iran [34], and China [33] to trimethoprim-sulfamethoxazole.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found a high rate of resistance to trimethoprim-sulfamethoxazole, cefazolin, and ampicillin in Shigella isolates. Theas resistance rates were in agreement with the reports published by Zamanlou et al [18], Nodeh Farahani et al [31], and Wang et al [32] in Iran and China, but higher than the results obtained by other researchers from China [33] to cefazolin, and Iran [34], and China [33] to trimethoprim-sulfamethoxazole.…”
Section: Discussionsupporting
confidence: 92%
“…32 Beladi et al reported the frequencies of TEM, CTX-M, and SHV genes in S. sonnei isolates as 60.87%, 21.74%, and 0%, and 58.3%, 16.6%, and 0% in S. flexneri isolates, respectively. 33 Hartman et al study on 459 tetracyclineresistant Shigella isolates reported the frequency of tetA and The represented numbers were the mean -SD of three independent repeats; 001, vB_SflS-ISF001; 002, vB_SsoS-ISF002; W4, Shigella sonnei W4; PTCC 1234, Shigella flexneri PTCC 1234.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ghannadi and colleagues, out of 52 Shigella isolates, more than 67% were MDR. The highest rates of resistance were observed for cephalothin, tetracycline, amikacin, trimethoprim-sulfamethoxazole, and ampicillin, while the lowest resistance rate was observed for ciprofloxacin (33). In this study, 36% of the examined isolates (n = 60) were MDR, and the highest resistance was observed for tetracycline and beta-lactam antibiotics (ampicillin and amoxicillin).…”
Section: Discussionmentioning
confidence: 47%
“…In their study, the bla TEM gene was found to be the most prevalent among Shigella isolates, followed by the bla CTX-M gene. The bla SHV gene was not detected in any of the isolates, indicating it was the least abundant (33). The bla SHV appears to have a low detection rate among Shigella isolates in Iran (42).…”
Section: Discussionmentioning
confidence: 84%